Calculation of the Heat Transfer Coefficient for Laminar Flow in Pipes in Practical Engineering Applications. Issue 20 (14th December 2018) - Jacimovic, Branislav; Genic, Srbislav; Lelea, Dorin
ABSTRACT: Paper presents an analysis of existing correlations for laminar liquid flow and heat transfer in tubes based on the published theoretical research and experimental data. Considering the relatively large deviation of existing correlations from the experimental data, the novel correlation for laminar heat transfer in tubes is proposed. The new correlation covers large range of tube diameters ranging from micro-scale level 125.4 µm to conventional diameter 20.8 mm, Graetz numbers up to 6500 and fluid to wall viscosity ratio 0.0048–11.7. Correlation ratio of the newly proposed relationship for a total number of 390 experimental runs is 96.6% and standard deviation is 16.2%. Moreover, correlation covers both the hydraulically and thermally undeveloped and developed flows and all cases of boundary conditions that can be met in industrial applications.